Upaya Meningkatkan Kompetensi Pedagogik Guru SDN 4 Jiken dalam Pemanfaatan Teknologi Komunikasi dan Informasi (TIK) Melalui Supervisi Akademik Teknik Kunjungan Kelas - Pujiati, Pujiati (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2019)
This research is a School Action Research (SAR) with the purpose to analyze theincreasing of the teachers’ pedagogical competenciesElementary School of 4 Jiken in theutilization of Communication and Informatical Technology (CIT) during the learning on thefirst Semester of the 2018/2019 year academic through academic supervision with classroomvisitation. The location of this research is Elementary School of 4 Jiken, Sub district of Jiken,Regency of Blora. The time of this research is early the first Semester of the 2018/2019 yearacademic according with the schedule and the research. The subjects of this research are theclass teachers (CT) and the subject teachers (ST) in Elementary School of 4 Jiken, Sub districtof Jiken, Regency of Blora, consist of five CT and three ST. Technique of collecting data ofthis research is non test technique. Whereas the instruments of collecting data of this researchare the sheets of observation and documentation. Technique of analyzing data of this researchis comparative description. The procedure of this research is using Cycle Model, consist offour steps; planning, action, observing and reflection. The results of this research are 1)academic supervision with classroom visitations to Elementary School of 4 Jiken teachers inthe utilization of Communication and Informatical Technology (CIT)during the learning on thefirst Semester of the 2018/2019 year academic are individually classroom visitation by thePrincipal and participation classroom visitation by the Principal with the teachers, 2) academicsupervision with classroom visitations to Elementary School of 4 Jiken teachers in theutilization of Communication and Informatical Technology (CIT) during the learning on thefirst Semester of the 2018/2019 year academic are composing slide power point and utilizingas the learning media in learning interaction and 3) the teachers’ pedagogical competenciesElementary School of 4 Jiken in the utilization of Communication and InformaticalTechnology (CIT) during the learning on the first Semester of the 2018/2019 year academicthrough academic supervision with classroom visitation are increasing and including as goodcategory (B).